Implementation of Cellular IoT over VANETs for Efficient Communication of Safety Messages - Channakeshava RN, Meenatchi Sundaram (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
when it comes to communication of road safety message communication, improved packet delivery ratio, reduced delay in packet delivery are most important as the messages are critical and need to be communicated and guaranteed delivery. Along with the better delivery parameters we energy efficiency is also an important factor. This paper introduces a method to implement VANETs using LTE-M against WAVE which is particularly concentrating on different types of communications in VANETs. With the adaption of LTE-M in the VANETs the model gives some design simplifications. This raise to reduction of unnecessary stages in cluster formation such as Cluster Heads in vehicles and allow communication of vehicles directly via RSU which will reduce the no of hops between sender and receiver when the cluster head is more than 2 hops from sender to receiver. This will also reduce the computation burden on cluster head. So we achieve better delivery ratio and reduced delay in delivering packets.